2010
DOI: 10.2478/s11686-010-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Lemuricola (Madoxyuris) bauchoti (Nematoda, Oxyuridae) from Lemur catta in Madagascar

Abstract: Lemuricola (Madoxyuris) bauchoti Chabaud, Brygoo et Petter, 1965 is redescribed from material collected from the ring-tailed lemur, Lemur catta, from the Beza Mahafaly Special Reserve in Madagascar using the scanning electron microscope. This is a new host record and the first oxyurid reported from the ring-tailed lemur. Previously, records of each species of the subgenus Madoxyuris have been restricted to a single host species, but the close relationship between these nematodes and their Strepsirrhini hosts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In their original descriptions of different species of Lemuricola Chabaud et al (1965) using light microscopy, described 3 pairs of pedunculated papillae, 2 pairs of sessile papillae, and 1 pair of amphids. In a previous study Robles et al (2010) demonstrated the presence of only 2 pairs of pedunculated papillae in L. (M.) bauchoti, a parasite of the ringtailed lemur, Lemur catta Linnaeus, in Madagascar. Using SEM microscopy, we also found only two pairs of pedunculated papillae (1st and 4th pairs) in L. (M.) vauceli.…”
Section: Discussionmentioning
confidence: 99%
“…In their original descriptions of different species of Lemuricola Chabaud et al (1965) using light microscopy, described 3 pairs of pedunculated papillae, 2 pairs of sessile papillae, and 1 pair of amphids. In a previous study Robles et al (2010) demonstrated the presence of only 2 pairs of pedunculated papillae in L. (M.) bauchoti, a parasite of the ringtailed lemur, Lemur catta Linnaeus, in Madagascar. Using SEM microscopy, we also found only two pairs of pedunculated papillae (1st and 4th pairs) in L. (M.) vauceli.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was sieved with tap water into a new tube, where parasite stages were sedimented by centrifugation at 450×g for 5 min. The sediment was transferred into a counting chamber and parasite eggs, oocysts, and larvae were microscopically classified into morphotypes, based on different references for primate (Cameron, 1930;Chabaud et al, 1965;Rosario Robles et al, 2010;Hugot et al, 1995;Hugot & del Robles, 2011;Irwin & Raharison, 2009;Kalousová et al, 2014;Little, 1966;Radespiel et al, 2015;Raharivololona, 2006Raharivololona, , 2009 as well as rodent parasites (Baker, 2006(Baker, , 2008Bowman et al, 2004;Dewi et al, 2018;Khalil et al, 2014;Petrzelkova et al, 2006;Sambon, 1924;Smales et al, 2009;Thomas, 1924).…”
Section: Parasite Identificationmentioning
confidence: 99%
“…and Lemurostrongylus sp. respectively, and coccidia oocysts; in Robles et al, 2010 found the oxyurid Lemuricola bauchoti , and Loudon and Sauther (2013) reported unidentified trichostrongylid eggs and Subulura sp. Villers et al (2008) , observed a significant difference in gastrointestinal parasites between wild and captive populations of L. catta through fecal examination.…”
Section: Introductionmentioning
confidence: 99%